Toán Lớp 8: (x+2)^2 + 2x + 4 x(x-2) + 6- x^2 = 2 x(x+2) – (x-2)^2 = 8 x(x-2) = x-2

Question

Toán Lớp 8: (x+2)^2 + 2x + 4
x(x-2) + 6- x^2 = 2
x(x+2) – (x-2)^2 = 8
x(x-2) = x-2, hướng dẫn giải giúp em bài này ạ, em cảm ơn thầy cô và các bạn nhiều.

in progress 0
Thanh Hường 1 tháng 2022-12-22T11:08:28+00:00 2 Answers 0 views 0

TRẢ LỜI ( 2 )

  1. \text{Milk gửi ẹ}????????

    \text{Giải đáp+ Lời giải và giải thích chi tiết:}

    (x+2)^2+2x+4

    =x^2+4x+4+2x+4

    =x^2+6x+8

    Vậy x=2

    ________________________

    x(x-2) + 6- x^2 = 2

    <=>x^2-2x+6-x^2=2

    <=>2x=4

    <=>x=2

    Vậy x=2

    ________________________

    x(x+2) – (x-2)^2 = 8

    <=>x^2+2x-(x^2-4x+4)=8

    <=>x^2+2x-x^2+4x-4=8

    <=>6x=12

    <=>x=2

    Vậy x=2

    ________________________
    x(x-2) = x-2

    <=>x(x-2)-(x-2)=0

    <=>(x-2)(x-1)=0

    <=>$\left[\begin{matrix} x-2=0\\ x-1=0\end{matrix}\right.$<=>$\left[\begin{matrix} x=2\\ x=1\end{matrix}\right.$

    Vậy x=2 hoặc x=1

  2. Giải đáp + Lời giải và giải thích chi tiết:

    (x+2)^2 + 2x + 4

    = x² + 4x + 4 + 2x + 4

    = x² + 6x + 8

    = ( x + 2)( x + 4 )

    x(x-2) + 6- x^2 = 2

    x² – 2x + 6 – x² = 2

    -2x + 6 = 2

    -2x = -4

    =>   x = 2
    x(x+2) – (x-2)^2 = 8

    x² + 2x – x² + 4x – 4= 8

    6x – 4 = 8

    6x = 12

    => x = 2
    x(x-2) = x-2

    x² – 2x = x – 2

    x² – 3x + 2 = 0

    ( x – 2 )( x – 1 ) = 0

    => x – 2 = 0

          x – 1 = 0

    => x = 2

         x = 1

     

Browse

12:2+4x4-12:2-5x3 = ? ( )